Technology-based learning media for enhancing digital literacy in elementary education: a conceptual and analytical review - Citra Hapsari Ekandari; Rida Fironika Kusumadewi; Yunita Sari; Yulina Ismiyanti (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
The development of information technology has triggered a major transformation in the world of education, particularly in efforts to improve digital literacy in elementary school students. The use of technology-based learning media is seen as one approach capable of providing a more interactive, relevant learning process, and in line with the needs of 21st-century competencies. This study seeks to examine in depth how various forms of digital media, such as educational applications, online learning platforms, and multimedia resources, can strengthen students' digital literacy skills. Using a literature review method, this study collected and interpreted findings from scientific journals, academic books, and various other publications related to the topic. The results of the study indicate that technology-based media not only help students access and understand digital information but also strengthen their skills in selecting, evaluating, and utilizing information ethically and responsibly. Furthermore, the use of digital media has been shown to increase students' learning motivation, active participation, and awareness of security and ethics in the digital space. Therefore, this study emphasizes the importance of targeted, planned, and sustainable technology integration so that elementary school students' digital literacy skills can develop optimally and in line with current developments.